Boys - Smile; Christensen, Mik; EMI Music (Denmark : EMI Music, 1999)
Contains four versions of the single.
CD 1 : Radio version / (3:07) -- Pasta Peoples Flufferboy radio edit / (3:10) -- Pasta Peoples Flufferboy mix / (5:30) -- Extended version / (4:20).
Koleksi Khas Wiramanja.
Title from disc label.
Keywords: Dance music